Utilization of plastic waste into fuel (fuel oil) in Namo Bintang Village, Deli Serdang Regency (Talenta Publisher, 2019)
Community service activities with the title: Utilization of Plastic Waste into Fuel Oil in Namo Bintang Village Deli Serdang Regency was planned in May to November 2019.This activity aim was to convert plastic waste into fuel which has economic value and is environmentally friendly. Community services implementation was by counselling, lectures, explanations of theories and techniques for processing plastic waste which was followed by the Namo Bintang Village Scavenger group, they listened and training to the material delivered by the community service team. Equipment for waste utilization is also very simple hence community groups can make it by themselves. Finally, monitoring and evaluation of the success of work in the field will be carried out by going directly to the field together, monitoring by visiting to find out whether the community can do it themselves.In addition, contact will be made by telephone to overcome the problems that arise.In general, community service activities have been successfully carried out and seen a good cooperative relationship between the Higher Education, especially the Implementation Team, and the community in Namo Bintang Village. Villagers realize the importance of saving the environment and at the same time improving their lives because they can make their fuel.